Effect of Dietary Zinc on Certain Blood Traits of Broiler Breeder Chickens - Al-Daraji , Hazim J.; Amen, Mahmood H.M. (International Journal of Poultry Science, 2011)
The aim of the present study was to evaluate the effect of zinc as feed additive on some the blood plasma traits of males and females of broiler breeder chickens. A total 132 (96 females and 36 males) of Cobb 500 broiler breeder chickens, 45 weeks old were used in this study. These birds were randomly distributed into four dietary treatment groups with three replicates each. Each treatment group constituted of 24 females and 9 males. Treatment groups were as following: T1: Birds fed the basal diet without any addition of zinc (0 Zn) (Control), T2: Birds fed diet supplemented with 50 mg Zn (pure zinc)/kg of diet, T3: Birds fed diet supplemented with 75 mg Zn (pure zinc)/kg of diet and T4: Birds fed diet supplemented with 100 mg Zn (pure zinc)/kg of diet. Results indicated that dietary zinc supplementation (T2, T3 and T4) resulted in significant (p<0.05) increase in blood plasma cholesterol, protein, calcium and phosphorus concentration and Alkaline Phosphatase (ALP) activity in broiler breeders males and females during 58 and 66 weeks of age and as regards the total means of these traits as compared with control group (T1). However, adding different levels of zinc to the diet (T2, T3 and T4) resulted in significant (p<0.05) increase in blood plasma glucose in broiler breeders males and females during 54, 58, 62 and 66 weeks of age and concerning the total mean of this trait. In conclusion, supplementing the diet of broiler breeder chickens with zinc caused significant increase in blood plasma traits included in this study. Therefore, zinc can be used as efficient feed additive for enhance physiological status of birds.